PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 039 AIR TERBIT KECAMATAN TAPUNG - ', Asiah; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Natural Sciences is a subject directly related to themselves and the natural surroundings. Based on the observations of the author as a fifth grade teacher at SDN 039 Air Terbit earned value data for science students is still low. It can be seen from the test of the first semester 2015, the number of students 28 and KKM set 75, the number of students who graduated KKM 10 people and the number of students who have not reached the KKM 18 with an average of 59.1. To improve learning, the researchers conducted a classroom action research approach Contextual Teaching and Learning (CTL). Based on the results of research conducted in April 2016 found that the activity of teachers has increased from 75% to 96.4% with very good category, activity of students has increased from 64.3% to 96.4% with very good categories, as well as increased yield student learning which at the beginning of the data individually, from 28 the average student learning outcomes of students amounted to only 59.1, the first cycle increased by 14.3% to 68.93 and the second cycle increased again by 25.3% from initial data becomes 79.1%. The completeness of students has increased from the initial data which there are only 10 students who completed the completeness value of 35.7%, in the first cycle has increased where there are 14 students who completed the completeness value by 50%, and the second cycle increased again to 24 students who completed the completeness value of 85.7%. This shows the classical completeness is fulfilled, which the classical completeness minimum is 75%. Keywords: CTL approach, learning outcomes of natural sciences